PERPINDAHAN PEMUKIMAN MASYARAKAT BAJO DARI PULAU MASUDU SULAWESI TENGGARA (Moving of Bajo Community Settlement From Masudu Island, South East Sulawesi) - Simon Sirua Sarapang (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2018)
The movement of people from one area to another can improve the structure of community settlements and socio-economic structures. This paper aims to determine the background of the settlement of the Bajo people from Masudu Island to the coast of Liano Village, the process of relocating the Bajo Community from Masudu Island to the coast of Liano Village, the settlement pattern of the Bajo Community, the socio-economic life of the Bajo community. Data collection consists of three types of study documents, interviews, and observations. The collected data is verified by two stages, namely: verification of internal data, and verification of external data. The next stage is the stage of interpretation which consists of analysis and synthesis. The results showed that the background of the movement of the Bajo people in Liano Village was a factor in the damage to houses due to strong winds and tides, the government policy of inadequate Bajo community income. The process of moving the Bajo community was carried out in stages, starting with the people who lived in the western part of Masudu Island in 1999, by crossing the sea and some people carrying home tools on Masudu Island. The pattern of settlement of Bajo people in the neighborhood Liano village is linearly following the highway with the distance between houses close together. The socio-economic life of the Bajo community in Liano Village is the creation of interactions with other communities on the land and the availability of infrastructure for the Bajo people so that they facilitate activities. ABSTRAK Perpindahan penduduk dari satu daerah ke daerah lainnya dapat memperbaiki struktur pemukiman masyarakat dan struktur sosial ekonomi. Tulisan ini bertujuan untuk mengetahui latarbelakang perpindahan pemukiman Masyarakat Bajo dari Pulau Masudu ke pesisir pantai Desa Liano, proses perpindahan pemukiman Masyarakat Bajo dari Pulau Masudu ke pesisir pantai Desa Liano, pola pemukiman Masyarakat Bajo, kehidupan sosial ekonomi masyarakat Bajo. Pengumpulan data terdiri dari tiga jenis yaitustudi dokumen, wawancara, dan observasi. Data yang telah dikumpulkan tersebut dilakukan verifikasi yang terdiri dari dua tahap yakni: verifikasi data internal, dan verifikasi data eksternal. Tahapan selanjutnya adalah tahap interpretasi yang terdiri dari analisis dan sintesis. Hasil penelitian menunjukan bahwa latar belakang perpindahan masyarakat Bajo di Desa Liano adalah faktor kerusakan rumah akibat angin kencang dan pasang air laut, kebijakan pemerintah penghasilan masyarakat bajo yang kurang mencukupi. Proses perpindahan masyarakat Bajo dilakukan secara bertahap yang diawali masyarakat yang tinggal di bagian Barat Pulau Masudu pada tahun 1999, dengan menyebrangi laut dan sebagian masyarakat membawa perkakas rumah yang ada di Pulau Masudu. Pola pemukiman masyarakat Bajo di Lingkungan Desa Liano berbentuk linear mengikuti jalan raya dengan jarak antara rumah saling berdekatan. Kehidupan sosial ekonomi masyarakat Bajo di Desa Liano adalah terciptanya interaksi dengan masyarakat lain yang ada di darat serta tersedianya prasarana bagi masyarakat Bajo sehingga mempermudah mereka dalam berbagai aktivitas.